Obstetric Admissions into the Intensive Care Unit in a Sub-urban University Teaching Hospital - Faponle, AF; Adenekan, AT (Nepal Journal of Obstetrics and Gynaecology, 2012)
Aims: Intensive care medicine is relatively young in developing countries and there are few studies showing obstetric utilization of the facilities in Intensive Care Units (ICU) in many developing nations. We sought to determine the ICU utilization by obstetric patients in our hospital, assess the spectrum of diseases necessitating admissions, the intervention required and outcome of such admissions. Methods: A 5 year retrospective review of all obstetric admissions into the ICU from January 2003 to December 2007. Subjects were included if they were admitted during pregnancy up to 42 days post partum. Data obtained included demographics, obstetric history, pre-existing medical problems, admission diagnosis, indication for ICU admission, intervention in the ICU and outcome. Results: Obstetric cases accounted for 1.5 % of total admissions into the ICU. These also represented 0.2% of total hospital deliveries. All the patients were admitted post partum. Eclampsia was the commonest primary obstetric diagnosis (58.8%) with neurological dysfunction as the commonest indication for ICU admission. Mortality rate among admitted cases was 41.2%. Conclusions: Obstetric patients form a small population of a third world multi-disciplinary ICU but mortality among this group was high. It is recommended that large obstetric units should establish there own ICUs with standard facilities which will facilitate improved care of critically ill pregnant women and thereby improve the outcome. NJOG 2011 Nov-Dec; 6 (2): 33-36 DOI: http://dx.doi.org/10.3126/njog.v6i2.6754